Care as Usual: An Acceptable Strategy to Apply During the COVID-19 Pandemic in a French Tertiary Gynecologic Oncology Department - Blache, Guillaume; El Hajj, Houssein; Jauffret, Camille; Houvenaeghel, Gilles; Sabiani, Laura; Barrou, Julien; Masquin, Isabelle; Le Saout, Jérémy; Mokart, Djamel; Faucher, Marion; Lambaudie, Eric (Frontiers in Oncology, 2021)
We describe and analyze a “care as usual” strategy of a French Comprehensive Cancer Center during COVID 19 pandemic to manage surgical patients with gynecological cancer. We conducted a retrospective analysis evaluating the surgical activity in our gynecologic oncology department between January 21st and May 12th, 2020. We compared the surgical activity, surgical and oncologic outcomes during the pre-lockdown period and the pandemic period. The main objective was to evaluate the impact of the COVID 19 pandemic on surgical activity. The secondary objectives were to analyze the surgical and the oncologic outcomes. We compared the surgical activity during the 8 weeks after the national lockdown (85 procedures) to the surgical activity in the 8 weeks preceding the lockdown (127 procedures). We observed a 33% decrease in activity between the 2 periods. The clinical and epidemiologic characteristics were similar between the two periods. There were no differences between the surgical approaches (p = 0.592), the surgical complexity (p = 0.323), the length of stay (p = 0.85) even for the complex procedure (p= 0.96), the perioperative (p = 0.791) and postoperative complication rates (p = 0.102). We observed a significant decrease in the time of return to intended oncological treatment (RIOT) during the lockdown period with an average of 31,9 days compared to 46,9 days in the pre-lockdown period (p = 0.003). During the COVID-19 pandemic, “care as usual” represents an acceptable strategy without impairing the oncologic outcome in a Comprehensive Cancer Center with a patient centered clinical pathway for gynecologic oncologic surgical patients.